RELIGIUSITAS MASYARAKAT PASCA BENCANA LAHAR DINGIN DI NAGARI BUKIK BATABUAH KECAMATAN CANDUANG KABUPATEN AGAM - Wahyu Tri Mustikarani; Silfia Hanani; Nunu Burhanuddin; Gazali Gazali (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The cold lava disaster in Nagari Bukik Batabuah caused physical damage, loss of property and family members, as well as profound social and psychological impacts. In this crisis, the community showed an increase in religiosity as a way of searching for meaning and a source of strength to face adversity. This study aims to examine the factors that influence the religiosity of the community and the forms of religiosity that developed after the disaster. The study uses a qualitative approach with a case study method through interviews, observation, and documentation. The results of the study show that there are four main factors that influence the religiosity of the community, namely education, experience, life, and intellect. This increase in religiosity is reflected in the emergence of social solidarity and a stronger sense of togetherness through disaster command posts, trauma healing, and religious activities that strengthen social and spiritual bonds. Thus, the disaster, which initially caused suffering, has become a turning point for the community to build a more religious, optimistic, and united life.